Evaluation of Salivary Cytokines for Diagnosis of both Trauma-Induced and Genetic Heterotopic Ossification - Sung Hsieh, Hsiao Hsin; Chung, Michael T.; Allen, Ronald M.; Ranganathan, Kavitha; Habbouche, Joe; Cholok, David; Butts, Jonathan; Kaura, Arminder; Tiruvannamalai-Annamalai, Ramkumar; Breuler, Chris; Priest, Caitlin; Loder, Shawn J.; et al. (Frontiers in Endocrinology, 2017)
Purpose Heterotopic ossification (HO) occurs in the setting of persistent systemic inflammation. The identification of reliable biomarkers can serve as an early diagnostic tool for HO, especially given the current lack of effective treatment strategies. Although serum biomarkers have great utility, they can be inappropriate or ineffective in traumatic acute injuries and in patients with fibrodysplasia ossificans progressiva (FOP). Therefore, the goal of this study is to profile the cytokines associated with HO using a different non-invasive source of biomarkers. Methods Serum and saliva were collected from a model of trauma-induced HO (tHO) with hind limb Achilles’ tenotomy and dorsal burn injury at indicated time points (pre-injury, 48 h, 1 week, and 3 weeks post-injury) and a genetic non-trauma HO model (Nfatc1-Cre/caAcvr1fl/wt). Samples were analyzed for 27 cytokines using the Bio-Plex assay. Histologic evaluation was performed in Nfatc1-Cre/caAcvr1fl/wt mice and at 48 h and 1 week post-injury in burn tenotomy mice. The mRNA expression levels of these cytokines at the tenotomy site were also quantified with quantitative real-time PCR. Pearson correlation coefficient was assessed between saliva and serum. Results Levels of TNF-α and IL-1β peaked at 48 h and 1 week post-injury in the burn/tenotomy cohort, and these values were significantly higher when compared with both uninjured (p < 0.01, p < 0.03) and burn-only mice (p < 0.01, p < 0.01). Immunofluorescence staining confirmed enhanced expression of IL-1β, TNF-α, and MCP-1 at the tenotomy site 48 h after injury. Monocyte chemoattractant protein-1 (MCP-1) and VEGF was detected in saliva showing elevated levels at 1 week post-injury in our tHO model when compared with both uninjured (p < 0.001, p < 0.01) and burn-only mice (p < 0.005, p < 0.01). The Pearson correlation between serum MCP-1 and salivary MCP-1 was statistically significant (r = 0.9686, p < 0.001) Similarly, the Pearson correlation between serum VEGF and salivary VEGF was statistically significant (r = 0.9709, p < 0.05). Conclusion In this preliminary study, we characterized the diagnostic potential of specific salivary cytokines that may serve as biomarkers for an early-stage diagnosis of HO. This study identified two candidate biomarkers for further study and suggests a novel method for diagnosis in the context of current difficult diagnosis and risks of current diagnostic methods in certain patients.